Periaural Music Player Daily Use Does Not Significantly Influence the Hearing Thresholds - Saralidze N.; Sharashenidze N.; Tushishvili M.; Kevanishvili Z. (Львівський клінічний вісник)
Introduction. The periaural music players are ones of the most popular among all the music devices used in the world. The maximal sound intensity in players reaches 100-120 dB. The users mostly use these devices in the noisy environments: while walking through the streets, transporting over, etc. In such situations the outer noise level approximates conventionally to 90 dB. To follow the applied melody, the music intensity in players should then exceed 90 dB thus being harmful for the delicate inner-ear structures The aim of the study is to compare the hearing function in periaural music player users and non-users. Materials and methods. In the randomized way, with the preliminary stratification by the absence of the outer and/or inner ear diseases (presence of cerumen, any outer- and/or middle-ear pathology and/or the history of auditory trauma, and/or the use of ototoxic drugs, and/or the family history of the hearing loss at early ages), diagnosed otoscopically, 277 students (174 females and 103 males – 62.8% and 37.2% correspondingly) at the age of 18-25 years old were included into the study. All of them were divided into periaural music players fans (experimental group – 150 persons, consisting of 101 females and 49 males – 67.3 % and 32.7% correspondingly), and persons that never or rarely used periaural music players (control group – 127 persons, consisting of 73 females and 54 males – 42.5% and 57.5 % correspondingly). The study included three steps: 1. The participants of the study underwent the otoscopy. 2. The participants filled the personal questionnaire. 3. The hearing thresholds of each person were determined in a soundproof chamber using audiometer. The obtained results were processed quantitively using the program IMB SPSS Statistics 20. Results. During the study the auditory threshold indices in the periaural music player users and non-users were estimated at 1-12-kHz frequency band. No difference in parameters was found at 1-6 kHz frequencies. The thresholds in periaural player music users exceeded those in non-users at higher frequencies – 8 and 12 kHz. Among 80 periaural music player users with the increase of the auditory thresholds at 12-kHz frequency, 54 persons had unilateral injury, while 26 – bilateral one. The threshold augmentation appeared thus twice as much unilaterally than bilaterally: 67.5% and 32.5% of cases, respectively. The hearing threshold augmentation at high auditory frequencies failed to correlate with the duration of periaural music player listening. The threshold augmentation at 12-kHz frequency was detected more often in users involved in periaural music player listening for more than 6 hours per day (54.2 %). On the other hand, the hearing impairment incidence was greater in persons that rarely (1-2 hours per day), than those who more intensively (3-6 hours per day), were listening to music using periaural music player daily – 48.6 % and 40.7 % respectively. Conclusions. 1. At conventional speech frequencies the hearing thresholds in periaural music player users were within the normal limits and statistically did not differ from those in non-users. 2. The hearing thresholds in periaural music player users were increased at high auditory frequencies (8 and 12 kHz). 3. Augmentation of hearing thresholds in periaural music player users at high auditory frequencies did not correlate with the daily durations of the player usage and, thus, had more individual-personal rather than systemic-group character. 4. The effects of periaural music player listening on the hearing function possess gender specific character: high-frequency hearing loss appears more often in females than in males.